Pelatihan Digital Marketing dan English for Hospitality Bagi Manajemen dan Staf Kasuari Exotic Resort Magelang - Sri Waluyo; Fatimah Nur Arifah; Ratih Laily Nurjanah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
The inclining situation of the Covid-19 pandemic has also pushed back the tourism economy, including hospitality. The purpose of this activity is to carry out community service activities with the general theme of capacity building at Kasuari Exotic Resort located in Bandongan Subdistrict, Magelang Regency, Central Java Province. The topics conveyed were about digital marketing and English for hotels. The target participants were management and staff at Kasuari Exotic Resort. This activity lasted for 3 (three) months starting from November 2022 to January 2023 in accordance with the agreement of both parties. This activity was carried out entirely in the Kasuari Exotic Resort Meeting Room. This activity involving a team of lecturers and students and the management and staff assigned from Kasuari Exotic Resort as participants. The materials given were Photography, Videography, English for Hospitality, Tourism Finance Management, E-Business, E-Commerce, Basic Web and SEO, and Digital Marketing